NEURO LINGUISTIC PROGRAMME ON ACADEMIC STRESS AND PERFORMANCE AMONG NURSING STUDENTS. (International Journal of Food and Nutritional Sciences, 2023)
A quasi-experimental design was undertaken to assess the effectiveness of Neuro Linguistic Program on academic stress and performance among nursing students in the selected nursing colleges, Chennai. A simple random technique was used to select the 200 students from 4 schools with100 in the study and 100 in the control group. Academic stress scale with 40 items were used to assess the academic stress of the first year B.Sc.(N) students. Their academic performance was assessed by their activities and assignments done in classes and the results of their formative and summative examinations. Findings of the study revealed that, in the study group, the calculated ‘t’ value for academic stress was 20.64 and the academic performance calculated ‘t’ value was 25.91 which is larger than p value at 0.001, which shows that there is a statistically high significant difference found between pre and post-test level of academic stress and performance. In addition, Correlation coefficient value in the study group (r = - 0.524) at p